2006
DOI: 10.1088/0957-4484/17/5/048
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation and quantum confinement in InGaN/GaN nanoposts

Abstract: Nanoposts of 10-40 nm top diameter on an InGaN/GaN quantum well structure were fabricated using electron-beam lithography and inductively coupled plasma reactive ion etching. Significant blue shifts up to 130 meV in the photoluminescence (PL) spectrum were observed. The blue-shift range increases with decreasing post diameter. For nanoposts with significant strain relaxation, the PL spectral peak position becomes less sensitive to carrier screening. On the basis of the temperature-dependent PL and time-resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 20 publications
3
59
0
Order By: Relevance
“…The QCSE, induced by the strain-induced internal electrical field, causes the spatial separation of confined electrons and holes in InGaN/GaN heterostructures and slows down the carrier recombination. 18,29,33 In the nanorods, the strain may be partially relaxed 1,2,8,9 and less internal electrical field will be present, leading to the faster relaxation in nanorods, 2 which is consistent with the power-dependent TIPL measurement as shown in Fig. 2 (e).…”
Section: × 10supporting
confidence: 79%
“…The QCSE, induced by the strain-induced internal electrical field, causes the spatial separation of confined electrons and holes in InGaN/GaN heterostructures and slows down the carrier recombination. 18,29,33 In the nanorods, the strain may be partially relaxed 1,2,8,9 and less internal electrical field will be present, leading to the faster relaxation in nanorods, 2 which is consistent with the power-dependent TIPL measurement as shown in Fig. 2 (e).…”
Section: × 10supporting
confidence: 79%
“…[3][4][5][6][7][8][9][10][11][12] The fabrication method has typically involved "top-down" patterning by etching an initially planar epitaxial structure containing InGaN/GaN QWs, although studies of directly grown nano-columnar structures have also been reported. 12 Correlations between spectroscopic results and numerical simulations of strain relaxation in the QWs were included in the reports by Yu et al 9 and Kawakami et al 10 The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a large, strain-induced electric field in III-N heterostructures often severely suppresses the oscillator strength of the exciton and, hence, the radiative decay rate and the internal quantum efficiency (IQE). Since strain is relaxed near free surfaces, nanodisks (NDs) in nanowires, which has a large surfaceto-volume ratio, have been widely considered as a promising solution for improving the IQE of InGaN/GaN photonic devices [4][5][6][7][8][9][10][11] . The accompanying improvement in the radiative decay rate is also important for realizing ultrafast singlephoton sources using InGaN/GaN QDs 3,12 .…”
mentioning
confidence: 99%